Using work system theory in a knowledge management tool for curriculum review process / Kalaimagal Ramakrishnan - Ramakrishnan, Kalaimagal (2013)
In 21st Century, there has been a growing concern about the role of Higher Education Institution (HEI) in producing competent graduates and how well they are satisfying the employers’ needs. In developing countries, HEI experiences a growing gap between their curricula and the demands from industry. According to the Malaysian Ministry of Human Resources (2011), almost all the universities today focus on how to increase the students’ competencies. However, preparing the students to meet the challenges of the future needs depends on the HEI curriculum. This study discusses the importance of Knowledge Management (KM) in HEI to enhance the curriculum review process to produce competent graduate. It uses Faculty of Computer Science and Information Technology (FCSIT), University of Malaya (UM) as a case study. This study uses mixed method viz questionnaires, interviews, and document analysis to collect data. The data collection involves 246 active current students and 147 graduated students, 20 academic and 12 non-academic faculty staff, 152 employers from industry and staff from other related departments in UM such as Centre for Industrial Training & Relations (CITRA) and Quality Management and Enhancement Centre (QMEC). Based on the findings, a KM tool has been developed to support the study. The results reveal strong support for the usefulness of KM approach in the HEI for enhancing the curriculum review process. The KM tool helps the HEI to compile the competencies required by the employers in the job market. It helps the HEI to generate curriculum based on industry’s need. By having curriculum derived from an industry’s needs, in the long run it will benefit the country to improve the composition of highly skilled workers to at least 37 per cent by 2015, to become a developed nation.